El hábitat rural disperso en la Península Ibérica durante la Antigüedad Tardía (siglos V-VII) - García Moreno, Luis A. (Antigüedad y Cristianismo, 1991)
Although there is a superabundance of documentation on the predominace of the agrupation of the habitats in the Iberian Peninsula during the late antiquity, in the fifth to eighth centuries it is obvious the existence of dispersed settlements. We have found the two types coexisting in certain areas and in others, with its own strongly defined settlement traditions, at times dominate the dispersed habitat model.